ANALISIS PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN PADA USAHA MANDIRI FURNICHIA FURNITURE DI KECAMATAN SUNGAI GELAM MENURUT PERSPEKTIF ISLAM - Suci Ramadani Harahap; Anzu Elvia Zahara; Nurfitri Martaliah (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
Furniture is a term that refers to objects that are used to support human activities in the room, such as sitting, lying down, eating, working, or storing goods. Furniture is an important part of the interior design of a room, because apart from its practical function, furniture also provides aesthetics and an atmosphere that is in accordance with the style and purpose of the room. The researcher uses qualitative research methods. Qualitative research methods are research approaches that focus on deep understanding of social phenomena or human life. This method collects and analyzes descriptive data, such as interviews, observations, or document analysis to explore meanings, patterns, and interpretations of the information collected on consumer behavior in different Furnichia Furniture independent businesses. Monthly income data obtained from research, it is known that some respondents in this study have their own way of determining the payment method used to buy furniture products. Some respondents who consume according to their financial capabilities will choose the cash payment method. And there are also those who do consumption, choosing the payment method in installments. Part of the consumption behavior of consumers in the independent business of Furnichia Furniture has not fully implemented the consumption guidelines taught in Islam. Consumption activities that are carried out sometimes just want to fulfill their desires without seeing the benefits. Buying Furniture products because they are influenced by friends or the environment so they don't think about whether the purchase is in accordance with their financial capabilities or not.